Creatine kinase kinetics in professional soccer players during a competitive season - Barbosa Coelho, D.; Figueiredo Morandi, R.; Anunciacao de Melo, M. A.; Silami Garcia, E. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2011)
Serum creatine kinase (CK) concentration has been widely used as an indicator of skeletal muscle damage in sports. However, there are no longitunal studies on post-game CK kinetics in Soccer during a competitive season. The aim of this study was to evaluate serum CK kinetics in professional Soccer players at different post-game times during a competitive season without training interruption. Seventeen professional soccer players (age: 22.2±3.1 years, height: 179±6.0 cm, body fat percentage: 9.5±1.1, and 67.0±3.5 mL O2/kg/min) were evaluated over a period of 3 months of the national championship. Serum CK concentration was measured before the beginning of the season (baseline) and at four different times after a soccer game (post-1: 12-20 h, post-2: 36-48 h, post-3: 60-65 h, and post-4: 90-110 h). Plasma CK concentrations were higher at all times when compared to baseline (p<0.05). Post-2 CK concentration was lower than post-1 and higher than post-3 and -4 (p<0.05), with no significant differences between post-3 and post-4. In conclusion, serum CK kinetics was influenced by the training routine of the soccer players, with a peak between 12 and 20 h after the game, returning to normal within 60-65 h. This procedure can be used to monitor the recovery state of athletes and game and training intensities.